Do foreign portfolio flows increase risk in emerging stock markets? Evidence from six Latin American countries (2011)
Foreign portfolio flows have been blamed for causing instability in emerging markets, especially during financial crises. This study measured the effect of foreign capital flows on volatility and exposure to world market risk in the six largest Latin American stock markets: Argentina, Brazil, Colombia, Chile, Mexico and Peru, for around 10 years including the 2008 World financial crisis. This will test whether these flows cause instability for those markets and increase their exposure to international stock market returns. A proprietary database, from Emerging Portoflio.com and time series models, both univariate (ARCH-GARCH) and multivariate (VAR), are used to estimate the effect foreign portfolio flows on the risk variables and the causality of these effects. We found no strong evidence to support the hypothesis that foreign flows cause instability in the Latin American stock markets, in spite of some evidence of causing price pressure. Instead, the evidence points to a strong dependence of market returns on international stock and foreign exchange markets, both in means and in volatility, instrumental to transmit crisis to those markets.